Legal Challenges of the Application of the Right to Be Forgotten in Blockchain in Indonesia and the European Union - Putri, Uni Tsulasi; Nurhayati, Irna; Rahman, Taufiq El (Universitas Negeri Gorontalo, 2025)
The Right to Be Forgotten (RTBF), as enshrined in data protection laws under Article 8 of the Indonesia’s Personal Data Protection Law (PDP Law) and Article 17 of the European Union (EU) General Data Protection Regulation (GDPR), grants individuals the right to request the deletion of personal data. However, this principle is fundamentally at odds with blockchain’s immutability, which ensures that once recorded, data cannot be altered or erased. This study examines the legal conflict between RTBF and blockchain through a doctrinal and comparative legal analysis of Indonesia and the EU regulatory framework. This study employs a normative legal research approach, utilizing doctrinal analysis and comparative legal method to examine statutory provisions, case law, and scholarly literature of Indonesia and the EU on the conflict between the RTBF and blockchain technology. Findings reveal that both jurisdictions struggle to reconcile RTBF enforcement with blockchain’s technical architecture, particularly in public networks. While the EU possesses stronger institutional maturity, it lacks clear jurisprudential direction on blockchain-based RTBF cases. Indonesia, with its evolving legal landscape, shows potential for flexible reinterpretation of “data destruction” under Article 44 of the PDP Law. The paper proposes a normative shift interpretation from the right to absolute erasure of the data itself toward the right to cryptographic erasure which supported by hybrid legal-technical solutions such as key deletion, off-chain storage, and permissioned blockchains.